Histoire, cinéma et idéologie : réflexions sur le Cimarron de Wesley Ruggles (1930) - Elyette Benjamin-Labarthe (Mise au Point)
Wesley Ruggles’s film adaptation of Edna Ferber’s eponymous novel deals with the question of slavery. Glorifying the right to set up, it eternalizes the famous uncivilized racing of 50 000 would-be farmers in quest of a piece of land in Oklahoma. The film pictures a place that punishes the appropriation of land by Anglo-american pioneers, but it avoids depicting a mixed-raced Texas peopled with men and women of African descent.